Host- and Species-Dependent Quasispecies Divergence of Severe Acute Respiratory Syndrome Coronavirus-2 in Non-human Primate Models - Hwang, Eun-Ha; Chung, Hoyin; Kim, Green; Oh, Hanseul; An, You Jung; Kang, Philyong; Ryu, Choong-min; Park, Jong-Hwan; Hong, Jungjoo; Koo, Bon-Sang (Frontiers in Microbiology, 2021)
Recently, newly emerging variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been continuously reported worldwide. However, the precise evaluation of SARS-CoV-2 microevolution in host is very limited because the exact genetic information of infected virus could not be acquired in human researches. In this report, we performed deep sequencing for seed virus and SARS-CoV-2 isolated in eight cynomolgus and rhesus macaques at 3 days post-inoculation and evaluated single-nucleotide polymorphisms (SNPs) in SARS-CoV-2 by variant analysis. A total of 69 single-nucleotide variants (SNVs) was present in the 5’-UTR, 3’-UTR, ORF1ab, S, ORF3a, ORF8, and N genes of the seed virus passaged in VERO cells. Between those present on the seed virus and those on each SARS-CoV-2 isolated from the lungs of the macaques, a total of 29 variants was identified in 4 coding proteins (ORF1ab, S, ORF3a, and N) and non-coding regions (5’ and 3’-UTR). Variant number was significantly different according to individual and ranged from 2 to 11. Moreover, the average major frequency variation was identified in 6 sites between the cynomolgus monkeys and rhesus macaques. As with diverse SNPs in SARS-CoV-2, the values of viral titers in lungs were significantly different according to individuals and species. Our study first revealed that the genomes of SARS-CoV-2 differ according to individuals and species despite infection of the identical virus in non-human primates. These results are important for interpretation of longitudinal studies evaluating the evolution of the SARS-CoV-2 in human beings and development of new diagnostics, vaccine and therapeutics targeting SARS-CoV-2.